Determinants of Farmers’ Participation in Off-Farm Activities in Iwo Local Government Area of Osun State - Salman , K. K.; Ufot, U. J. (The Nigerian Journal of Rural Extension and Development, 2023)
Income constraint has been the major problem faced by farmers in rural areas for many years. This has significantly reduced agricultural production and the standard of living of farmers. In this study, factors responsible for farmers’ participation in off-farm employment activities, various off-farm activities engaged, the extent of participation and the share of off-farm income in the total income of farmers were examined. A stratified random sampling technique was used in the selection of 90 respondents from Iwo local government area of Osun state. Descriptive statistics such as frequencies and percentages were used to describe the socioeconomic characteristics of farmers while binary logistic regression was used to determine the factors that influence farmers’ participation in off-farm activities. The study reveals that majority of farmers (63.3%) participated in one form of off-farm activities or the other. The average farm income was found to be N46,911.11±28,321.8 per annum and the average off-farm income was N80,935.56±36,007.9 per annum. The study provides evidence that, off-farm income contributed more than farm income to the total income of farmers accounting for 63.3 % of their total income. The off-farm activities in the study area included paid employments as well as self-employments. Results further show that the average farm size cultivated in the study area was approximately 1.77±1.3 hectares and the average number of years of formal education of farmers was 6.04±4.7 years. Age, household size, remittance and the local area characteristics were found to be significant as determinants of participation in off-farm income activities. In conclusion, despite farming being the major occupation of all the respondents, majority of them were involved in one form of off-farm activities or the other. Intervention programmes and incentives should be channelled to low income farmers to encourage sustainable engagement in farming.